Willingness to Communicate, Multilingualism and Interactions in Community Contexts - Alastair Henry; Peter D. MacIntyre (Multilingual Matters, 2024)
This book presents the findings of an in-depth qualitative longitudinal investigation into the willingness to communicate (WTC) of individuals who, through varying migration channels, left one cultural/linguistic context to make a new life in another. It examines communication behaviours and language choice in multilingual community contexts and emphasises how even the most trivial of communication events are embedded in histories of previous communication and are influenced by emotions connected with a person's overall life situation. The book fills a gap in contemporary WTC research by examining how WTC operates in multilingual community contexts. Through the use of a complexity lens and the presentation of a revised 3D pyramid model, the authors demonstrate the dynamic nature of WTC and shed new light on processes that affect communication, migration and well-being. This book will be of interest to researchers seeking to explore individual differences using context sensitive and temporally focused designs. This book is open access under a CC BY ND licence.